Primary Sjögren’s Syndrome of Early and Late Onset: Distinct Clinical Phenotypes and Lymphoma Development - Goules, Andreas V.; Argyropoulou, Ourania D.; Pezoulas, Vasileios C.; Chatzis, Loukas; Critselis, Elena; Gandolfo, Saviana; Ferro, Francesco; Binutti, Marco; Donati, Valentina; Zandonella Callegher, Sara; Venetsanopoulou, Aliki; Zampeli, Evangelia; et al. (Frontiers in Immunology, 2020)
Objectives To study the clinical, serological and histologic features of primary Sjögren’s syndrome (pSS) patients with early (young ≤35 years) or late (old ≥65 years) onset and to explore the differential effect on lymphoma development. Methods From a multicentre study population of 1997 consecutive pSS patients, those with early or late disease onset, were matched and compared with pSS control patients of middle age onset. Data driven analysis was applied to identify the independent variables associated with lymphoma in both age groups. Results Young pSS patients (19%, n=379), had higher frequency of salivary gland enlargement (SGE, lymphadenopathy, Raynaud’s phenomenon, autoantibodies, C4 hypocomplementemia, hypergammaglobulinemia, leukopenia and lymphoma (10.3% vs 5.7%, p=0.030, OR=1.91, 95% CI: 1.11-3.27), while old pSS patients (15%, n=293), had more frequently dry mouth, interstitial lung disease and lymphoma (6.8% vs 2.1%, p=0.011, OR=3.40, 95% CI: 1.34-8.17), compared to their middle-aged pSS controls respectively. In young pSS patients cryoglobulinemia, C4 hypocomplementemia, lymphadenopathy and SGE were identified as independent lymphoma associated factors, as opposed to old pSS patients in whom SGE, C4 hypocomplementemia and male gender were the independent lymphoma associated factors. Early onset pSS patients displayed two incidence peaks of lymphoma within 3 years of onset and after 10 years while in late onset pSS patients, lymphoma occurred within the first 6 years. Conclusion Patients with early and late disease onset constitute a significant proportion of pSS population with distinct clinical phenotypes. They possess a higher prevalence of lymphoma, with different predisposing factors and lymphoma distribution across time.